Tremors [videorecording (DVD)] - Underwood, Ron; Bacon, Kevin, 1958-; Ward, Fred, 1942-; Gross, Michael, 1947-; McEntire, Reba (Universal Home Video, 1998)
Two country handymen and a seismology student discover a desolate town infested with gigantic man-eating creatures that live underground.